(untitled) ("Temas Sociais" Journal, 2024)
Despite the significant advances in treatment, social issues continue to have an impact on people with HIV, who are still the victims of on people with HIV, who are still victims of derogatory terms that renew prejudice. This study presents the results of a descriptive study of mixed descriptive study that aimed to understand whether individuals experienced situations of discrimination in formal and informal relationships after learning about the disease. Data was collected using a Google Forms questionnaire applied to 10 people living with to 10 people living with HIV who are followed up at the Abraço Association in the CAAP service. Of the 10 individuals surveyed, the feeling of discrimination is present in just under half of them (4 cases), except the labour camp, where the majority didn’t feel comfortable sharing their diagnosis, probably for fear of discrimination and other consequences. These results could be related to the fact that the individuals surveyed had been diagnosed for some time. This could lead to a more relaxed and informed attitude towards the situation and a time distance from their feelings when sharing their diagnosis. Despite this, we can’t help but highlight the existence of situations of discrimination in the most informal and intimate groups, the lack of information about the diagnosis in the workplace and, on the other hand, the idea that discrimination is associated with a lack of (or wrong) information, so increasing information to the general population could be a strategy to combat discrimination.